PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL PEMBELAJARAN LEARNING CYCLE 6E PADA MATERI GETARAN DAN GELOMBANG SMP - Nunung Fitriani; Azhar Azhar; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Learning devices based on the 6E learning cycle model are a series of processes or activities carried out to produce a medium or means used and prepared by the teacher in the learning process. The learning tools developed are Learning Implementation Plans (RPP), Student Worksheets (LKPD), and learning outcomes tests.The main objective of this study is to develop RPP learning tools, LKPD and learning outcomes tests based on the 6E learning cycle model on the material of vibrations and waves of SMP. The development of this learning tool uses the method of research and development of research and development (R&D) In this research the validation stage is conducted by 3 validator lecturers. Data analysis on using descriptive analysis by calculating the index of each indikator used to determine the validity of the RPP, LKPD and learning outcomes tests developed. The results of this study obtained an average RPP validity of 3,54 with a very high category and declared valid, the average validity of LKPD is 3,40 with a very high category and declared valid, the average validity of learning outcomes tests is 3,52 with very high category and declared valid. So as a whole the average validity of learning devices (RPP, LKPD, and test results of learning) based on the learning cycle 6E model developed on the material of vibrations and waves of junior high schools obtained an average value of 3,49 with a high category and was declared valid and feasible to use as teaching materials in schools to support the teaching and learning process so that it becomes better.Key Words: Learning Devices (RPP, LKPD, and learning outcomes test), learning cycle 6E, vibration and waves